Anxiety and depression among patients with alcohol dependence: co-morbid or substance-related problems?. (10th July 2017) - Gallagher, C.; Radmall, Z.; O'Gara, C.; Burke, T.
Abstract : Objectives: There are conflicting reports on the levels of anxiety and depression in individuals with alcohol problems and whether these conditions are substance-related or independent of the alcohol problem. The aim of this study was to characterise rates of co-morbid psychiatric symptoms among a group of individuals commencing treatment for alcohol dependence, and to examine the stability of these symptoms following treatment of the alcohol problem. Methods: Symptoms of anxiety and depression were examined in a group of individuals ( n =93) undergoing residential treatment for alcohol dependence. Symptoms were measured at treatment entry and again at treatment completion using the Beck Anxiety Inventory and the Beck Depression Inventory – II. Results: High levels of anxiety and depressive symptoms were reported at treatment entry, but on completion of treatment (28 days later) the majority of participants were no longer reporting symptoms suggestive of a possible co-morbid condition. Conclusions: The significant change in rates of reported symptoms following completion of treatment suggests that a large proportion of symptoms reported at treatment entry were substance related. Diagnosing co-morbid conditions is best left until after a period of abstinence during which the alcohol problem has been treated. Assessing for co-morbidity at time of treatment seeking is likely to result in inappropriate co-morbid diagnoses being made and inappropriate or unnecessary treatments being prescribed for such individuals.